CLINICAL PHARMACOLOGY OF DRUGS USED IN THE TREATMENT OF EPILEPTIC SYNDROME - Parpiyava Salima Bokijonovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article provides a comprehensive overview of the clinical pharmacology of antiepileptic drugs (AEDs) used in the management of epileptic syndrome. It explores the mechanisms of action, pharmacokinetics, therapeutic indications, drug selection based on seizure type, and safety profiles of traditional and newer AEDs. Special emphasis is placed on personalized treatment strategies, drug interactions, and pharmacoresistance in epilepsy. The article aims to support rational, evidence-based pharmacological interventions for improved seizure control and patient outcomes.